Vitamin D Supplementation and Colorectal Cancer Patients Outcomes - Mulyadi, Noeray Pratiwi; Rudiman, Reno; Purnama, Andriana (Faculty of Medicine, Universitas Padjadjaran, 2024)
Colorectal cancer is the third most encountered malignancy worldwide in 2018. Some earlier studies indicate a significant influence of vitamin D supplementation on the 5-year survival rate and the rate of metastasis progression in colorectal cancer patients. Studies investigating the effects of vitamin D supplementation on the outcomes of colorectal cancer patients are limited in Indonesia. Therefore, a double-blinded Randomized Controlled Trial (RCT) of the effect of vitamin D supplementation on the outcome of colorectal cancer patients was conducted from April 2022 to March 2023 at the digestive surgery outpatient clinic of Dr. Hasan Sadikin General Hospital Bandung, Indonesia. In this study, 36 patients received vitamin D and 34 patients received a placebo. Data analysis performed using the multivariate analysis with multiple regression revealed no significant relationship between vitamin D supplementation and colorectal cancer patient outcomes. Furthermore, ANOVA analysis indicated no relationship between the analyzed independent and dependent variables in this study. No relationship was found between vitamin D supplementation and the outcomes of metastasis, mortality, and Karnofsky scores in colorectal cancer patients. Further research with a larger population is still needed to determine the benefits of vitamin D supplementation on the outcomes of colorectal cancer patients.